Kinetics of polyisoprene oxidation in the presence of active chemical additives - A. S. Kazakova; O. V. Karmanova; Y. F. Shutilin (Тонкие химические технологии, 2010)
Analysis of changes in the structure and properties of polyisoprene films was carried out. The samples contained chemically active additives (antioxidants, antiscorchings) and were subsequenly warmed up.